2019
DOI: 10.24926/iip.v10i1.1637
|View full text |Cite|
|
Sign up to set email alerts
|

Framework for Patient Safety

Abstract: A commitment on quality objectives is a crucial element of quality policy in HROs, such as hospitals and other healthcare institutions. The quality of care includes objectives related to effectiveness, efficiency, and a patient’s experience. Healthcare organizations are also aware of the importance of promoting safety practices and the resiliency analysis of the clinical practice in order to improve quality. Patient Safety Culture has been defined as the product of individual and group values, attitudes, compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The intersection of drugs, devices, and biologics in combination products creates a complex regulatory environment. Understanding and navigating this landscape is crucial for manufacturers, regulators, and healthcare professionals to ensure that these products meet rigorous safety and efficacy standards ( 59 ).…”
Section: Significant Importance In the Field Of Pharmaceuticals And N...mentioning
confidence: 99%
“…The intersection of drugs, devices, and biologics in combination products creates a complex regulatory environment. Understanding and navigating this landscape is crucial for manufacturers, regulators, and healthcare professionals to ensure that these products meet rigorous safety and efficacy standards ( 59 ).…”
Section: Significant Importance In the Field Of Pharmaceuticals And N...mentioning
confidence: 99%
“…11 One of the important tasks of nurses is to provide correct medication while maintaining the patients' safety, which requires proper knowledge and performance as any defect in the medication knowledge of the nurses can lead to irreversible damage or death of the patient. 12,13 In this regard, no specific study has been conducted on nurses' knowledge resources. However, it has been shown that nurses use the results and the suggestion of researches and studies in their practice and tend to increase patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%